2017
DOI: 10.18535/ijecs/v6i3.31
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Text Segmentation Techniques

Abstract: This paper represents the text segmentation is an important process of image processing and understanding. Basically it is defined as the process of dividing the image into different parts of homogeneity. The aim of text segmentation is to simplify the representation of an image into something that is more meaningful and easier to understand.So the overall objective is to represent the nearest neighbor criteriaon for grouping components in the same line which results in clusters as well as large dataset contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Chlorpromazine (CPZ), for example, is used to treat psychotic disorders, such as schizophrenia or manic-depression, in adults. 66 Some studies reported that phenothiazine derivatives, including CPZ, may affect the formation of CCVs and then inhibit CME. 67,68 Similarly, during viral infection, chloroquine inhibits the formation and functioning of CCVs and its analogs inhibit the acidification of endosomes.…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%
“…Chlorpromazine (CPZ), for example, is used to treat psychotic disorders, such as schizophrenia or manic-depression, in adults. 66 Some studies reported that phenothiazine derivatives, including CPZ, may affect the formation of CCVs and then inhibit CME. 67,68 Similarly, during viral infection, chloroquine inhibits the formation and functioning of CCVs and its analogs inhibit the acidification of endosomes.…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%
“…Many of the drugs synthesized were originally designed to treat other indications, and their final designation was still the matter of chance finding [ 2 ]. The discovery of chlorpromazine as an antipsychotic, for example, is often described as ‘serendipitous’, as it was originally synthesized for nausea and allergies; however, it was observed that it induced calmness when given to patients [ 3 ]. Other examples include the anxiolytic meprobamate, which was first used as an antimicrobial therapy [ 4 ], or the MAOI antidepressants that were first tried in tuberculosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%